(untitled) (Sociologisk Forskning, 1994)
Whatever happened, happened. Some notes on inner logic, especially in organizations The notion that social events partly arise as a consequence of inner logic, i.e. that patterns and structures emerge outside of, or even in opposition against, plans and goals is a common element in social science. Inner logic is a summary term for social processes developing autonomously, i.e. without any individual or group intending them. Organizations quite often contain inner-logic processes. If, as this author maintains, fruitful organization theory has to build on rationalistic assumptions, how then do we handle instances of inner logic? A first step may be to break up the traditional link between structuralism and functionalism, maintaining the former and rejecting the latter. Organizations are intentionally dynamic, i.e. depend on order and predictability. To the extent that inner-logic processes appear in organizations, they should be analysed as confrontations between opposing rationalities rather than as spontaneous reactions of a ”system” . Also, frequently recurring organizational forms such as hierarchy are more fruitfully regarded as e.g. transaction-cost outcomes rather than as functional responses to system needs. Rationalism and structuralism are compatible, rationalism and functionalism are not.